Ecosystem services, biodiversity and environmental change in a tropical mountain ecosystem of South Ecuador - Bendix, Jorg (Ecological Studies, Analysis and Synthesis, 2013)
An interdisciplinary research unit consisting of 30 teams in the natural, economic and social sciences analyzed biodiversity and ecosystem services of a mountain rainforest ecosystem in the hotspot of the tropical Andes, with special reference to past, current and future environmental changes. The group assessed ecosystem services using data from ecological field and scenario-driven model experiments, and with the help of comparative field surveys of the natural forest and its anthropogenic replacement system for agriculture. The book offers insights into the impacts of environmental change on various service categories mentioned in the Millennium Ecosystem Assessment (2005): cultural, regulating, supporting and provisioning ecosystem services. Examples focus on biodiversity of plants and animals including trophic networks, and abiotic/biotic parameters such as soils, regional climate, water, nutrient and sediment cycles. The types of threats considered include land use and climate changes, as well as atmospheric fertilization. In terms of regulating and provisioning services, the emphasis is primarily on water regulation and supply as well as climate regulation and carbon sequestration. With regard to provisioning services, the synthesis of the book provides science-based recommendations for a sustainable land use portfolio including several options such as forestry, pasture management and the practices of indigenous peoples. In closing, the authors show how they integrated the local society by pursuing capacity building in compliance with the CBD-ABS (Convention on Biological Diversity - Access and Benefit Sharing), in the form of education and knowledge transfer for application.